Reboot! Reimagining Physically Active Lives: 2022 Australian Report Card on Physical Activity for Children and Young People - Hesketh, Kylie; Lubans, David; Cleland, Verity; Gomersall, Sjaan; Reece, Lindsey; Ridgers, Nicola; Straker, Leon; Stylianou, Michalis; Tomkinson, Grant; Booth, Verity; Olds, Tim (My University, 2022)
Active Healthy Kids Australia, using a research working group, produces reports cards on the physical activity of children and young people in Australia. Scoring key indicators, the report card uses available national and state based data sets to inform the grade. The Australian report card contributes to the Global Healthy Kids Alliance where several countries report on the same indictors as an international consortium.
Keywords: Childhood and child development; Health and wellbeing